Palliative surgery of the C.B.P. - Pomi, Jorge; Bogliaccini, Gustavo; Chifflet, Juan; Bertullo, Hugo (Cirugía del Uruguay, 1982)
Palliative surgery in lung cancer is analyzed which is defined and differenciated from incomplete and cytoreductive resection. It has 4 inidications: thoracic pain, puhnonary abcesses, massive hemoptysis and pneumic hipertrophic osteoarthopathy. Neumothórax and pleural effusion are not considered in this group.